Preparation and oxygen permeation properties of SrCo0.9Nb0.1O3-d hollow fibre membranes - Meng, B.; Wang, Z.; Liu, Y.; Tan, X.; da Costa, J.; Liu, Shaomin (Pergamon, 2011)
Ultrafine SrCo0.9Nb0.1O3− δ (SCNb) perovskite powders were synthesized by a modified Pechini method using EDTA and citrate acid as chelating agents. Dense SCNb hollow fibre membranes with an asymmetric structure were fabricated via a phase inversion and sintering technique. Oxygen permeation fluxes through the obtained hollow fibre membranes were measured in the temperature range of 500–900 °C under air/helium gradients. The results indicated that the oxygen permeation flux through the SCNb hollow fibre membrane was approximately 9.30mmol m−2 s−1 at 650 °C when the air feed and the helium sweeping rates were 74.4 µmol s−1 and 44.6 µmol s−1, respectively. The SCNb hollow fibre membranes showed a stable oxygen permeation flux over 240 h at 900 °C with a maximum value reaching 38.10mmolm−2 s−1 comparing favorable to the performance of other perovskite membranes.